3D Geospatial database using land adminisration domain model (LADM) for strata title management [electronic resource] - Nurul Natasha Nasorudin, 1991-, author (2015)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2015